Pelatihan Penggunaan Media Pembelajaran Artificial Intelligence dalam pembelajaran Deep Learning bagi Guru Bahasa Inggris - Basuki Basuki; Titi Rokhayati; Yuli Widiyono; Ari Fajar Isbakhi; Bening Zulfa (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This community service program is designed to enhance the competence of English teachers at SMP N 33 Purworejo in utilizing Artificial Intelligence (AI)-based learning media, particularly deep learning technology. In the digital era, many teachers still face limitations in integrating intelligent technology into classroom activities, which affects the effectiveness of learning. The program was carried out in four stages: the provision of basic materials on AI and deep learning, technical training on the use of AI applications, practical development of learning media, and mentoring combined with evaluation. The results of this activity show an increase in teachers’ understanding and skills in operating AI tools, with each participant producing at least one AI-based learning media product. Through workshops, teachers learned to use applications such as chatbots, speech-to-text, text-to-speech, and AI-assisted language tools to enrich students’ learning experiences. In addition, teachers were guided to design contextual media tailored to curriculum goals and student needs. Mentoring ensured that the products created were tested, improved, and ready to be applied in the classroom. The novelty of this activity lies in its focus on practical implementation of deep learning in junior high school English teaching, positioning teachers not only as users but also as creators of innovative media. Beyond technical competence, this program fosters collaboration among teachers to sustain innovation. In the long term, the outcomes are expected to improve students’ engagement, motivation, and communication skills, and contribute to the establishment of a digital learning ecosystem that supports interactive, effective, and future-oriented education.